RETRACTED: The value, diagnostic efficacy and clinical significance of functional magnetic resonance imaging in evaluating the efficacy of neoadjuvant chemotherapy in patients with triple negative breast cancer - He, Xiaoping; Wang, Zongsheng; Zhou, Ying; Feng, Yongli (Frontiers in Oncology, 2023)
Background: Breast cancer (BC) is a common malignant tumor in female. In recent years, with the change of fertility pattern and lifestyle, the incidence of breast cancer is increasing year by year, seriously endangering the health and life of women. MRI is suitable for follow-up evaluation of the course of neoadjuvant chemotherapy in LABC, but there are few related studies and reports. Based on the above background, it is necessary to further evaluate the value of functional magnetic resonance imaging in neoadjuvant chemotherapy in patients with triple negative breast cancer, so as to lay a theoretical foundation for the popularization and application of this detection method. Based on this, this study was to explore the value, diagnostic efficacy and clinical importance of functional magnetic resonance imaging in evaluating the efficacy of neoadjuvant chemotherapy in patients with triple negative breast cancer. Methods: A total of 62 patients with triple-negative breast cancer who received neoadjuvant chemotherapy in our hospital from September 2017 to September 2022 were selected. Results: There was no significant difference between the mode of tumor withdrawal and the pathological complete remission of tumor tissue (P>0.05). There was no significant difference in anti-Trop-2 antibody-drug conjugates (ADC) data before and after chemotherapy between over-expressed patients with human epidermal growth factor receptor-2 (HER-2) and non-over-expressed patients with HER-2 (P>0.05). The levels of ADC and Δ ADC in pathological complete remission patients after chemotherapy were significantly higher than those in non-pathological complete remission patients (P<0.05). Using the ΔADC value as the evaluation parameter, the pathological response of tumor tissue was classified as the "gold standard" to draw the ROC curve, the area under curve (AUC) was 0.673, the cut-off of ΔADC to evaluate the significant response of tumor tissue after chemotherapy was 1.418, the sensitivity of evaluating the efficacy was 71.9%, and the specificity was 55.0%. Conclusion: Functional magnetic resonance imaging (fMRI) has diagnostic value for neoadjuvant chemotherapy in patients with triple negative breast cancer. According to the change of ADC value, the curative effect can be predicted early and the treatment strategy can be adjusted in time.